PENGARUH BIMBINGAN IMAJINASI MENGGUNAKAN MEDIA AUDIO VISUAL (VIDEO) TERHADAP STRES HOSPITALISASI ANAK DI RS ISLAM SURABAYA - Nurul Chusniyah; Wesiana Heris Santy (Universitas Nahdlatul Ulama Surabaya, 2016)
that should be taken in order to reduce stress. The purpose of the study to determine the influence of guided imagery using a video to the stress of hospitalization in children Islamic Hospital Surabaya. Design using Quasy Experiment with the approach pre-post test. The population of all children (6-9 years) were treated. Samples of 24 respondents using simple random sampling. The data were analyzed with the Wilcoxon test and Mann-Whithney test with α = 0.05. The results of research in the treatment group pretest majority (58.3%) experienced moderate stress, in the control group half (50%) also moderate stress. After the guide imagery, the treatment group was almost entirely (83.3%) experienced mild stress, whereas most of the control group (58.3%) remained moderate stress. Their mean delta difference in the treatment group at 5.50 and 0.002 Wilcoxon test results, while the control group their mean delta 0.33 with 0.236 Wilcoxon test results. Mann-Whitney test results showed p (0.004) <α (0.05),then H0 is rejected means that there is influence between guided imagery using avideo with the stress of hospitalization of children of school age.The conclusions ofresearch that guided imagery using video media influence to decrease stress levels ofhospitalization of children, are expected to be used as guide imagery as nursingactions effort to reduce the stress of hospitalization in children.